Geographic variation in the duets of the Rufous-naped Wren (Campylorhynchus rufinucha) complex - Ku Peralta, Wiliam (2020)
Acoustic signals used in animal communication play a key role in mate attraction, species recognition, and territory defense. Variation in acoustic signals may reflect population structure, lack of gene flow, and phylogenetic relationships. In birds, the study of geographic variation in acoustic signals has been useful for elucidating potential factors involved in phenotypic divergence and for establishing species limits. However, most of the studies on geographic variation have focused on calls and solo songs, with few studies focusing on complex behaviors such as duets. In this study, we investigated the variation in the duets of the Rufous-naped Wren (Campylorhynchus rufinucha). Our results suggest that duets vary across the distribution range of the species complex, matching the 3 taxonomic groups previously suggested (rufinucha, humilis, and capistratus). We also found a marked song sexual dimorphism in 2 groups, rufinucha and humilis, that is lacking in capistratus. At the local level, we found that duets also vary among sites within groups, but less than between groups. Our results suggest that groups rufinucha and humilis sing the most similar duets, whereas capistratus performs the most divergent duets of the 3 groups. Further, when comparing duet variation across geography, we found that birds living closer to each other sing more similar duets. We suggest that the existence of 3 vocal lineages is probably the result of historical geographic isolation followed by other selective (i.e. sexual selection, social selection, habitat structure) and/or non-selective factors (i.e. drift, isolation by distance), and that variation found within groups may be the result of cultural drift or social selection.